Formulation and In Vitro Evaluation of Mupirocin-loaded Alginate Microspheres - Shanmugam, V. (Asian Journal of Pharmaceutics (AJP), 2016)
Introduction: Mupirocin (pseudomonic acid A) is a topical antibiotic used for the treatment of impetigo a superficial infection of the skin. Aim: The goal of this study was to evaluate the technological feasibility of delivering antibiotic using alginate microspheres. Materials and Methods: Microspheres were prepared by emulsification method using sodium alginate as a polymer and calcium chloride (CaCl2) as a cross-linking agent. In this investigation, a novel method was used to investigate the joint influence concentration of alginate and CaCl2 in a blend of liquid paraffin in the dispersion medium. Potential variables such as the concentration of drug and sodium alginate: Drug ratios were kept constant in the experimental design. Different concentrations of the cross-linking agent and different time periods of the cross-linking process were used to change the extent of cross-linking. The cross-linked microspheres were characterized by evaluating the extent of cross-linking, the morphology, and drug loading and in vitro studies of drug release. Results and Discussion: The particle size of the drug loaded microspheres was 75 Î¼m, and they have narrow size distribution. Total drug loading was determined to be 15.10 Â± 0.01. Preparation process gave a yield production of nearly 80% for the prepared batches. The microspheres released 71.3% of mupirocin at 72 h. Conclusion: The study revealed that for obtaining controlled delivery of mupirocin; the microspheres should be prepared using relatively an optimum concentration of sodium alginate and CaCl2 and in the dispersion medium.